2021
DOI: 10.1007/s40037-021-00676-7
|View full text |Cite
|
Sign up to set email alerts
|

Does being a coach benefit clinician-educators? Amixed methods study of faculty self-efficacy, job satisfaction and burnout

Abstract: Introduction Coaching is a growing clinician-educator role. Self-efficacy is a powerful faculty motivator that is associated positively with job satisfaction and negatively with burnout. This study examines self-efficacy, job satisfaction, and burnout in coaches and other clinician-educators. Methods We conducted a mixed methods study using a quantitative survey followed by qualitative interviews of faculty at the University of California, San Francisco. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 48 publications
2
6
1
Order By: Relevance
“…Elster et al's previously mentioned mixed methods analyses found that nearly 2/3 of academic physicians who were trained and paid to coach medical students met criteria for burnout on the MBI. It is unclear why rates of burnout in Elster's study are different from ours, though there are likely factors specific to the institution or setting [7].…”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations
“…Elster et al's previously mentioned mixed methods analyses found that nearly 2/3 of academic physicians who were trained and paid to coach medical students met criteria for burnout on the MBI. It is unclear why rates of burnout in Elster's study are different from ours, though there are likely factors specific to the institution or setting [7].…”
Section: Discussioncontrasting
confidence: 73%
“…Both Elster et al's and Brooks et al's studies of medical student coaches revealed similar themes that could contribute to a coach's professional satisfaction or fulfillment, such as guiding struggling trainees, building a longitudinal relationship, and observing their successes [6,7]. Coaches in both studies were challenged by the fragmentation of one's professional identity due to the coaching role and the expectations and burden this carried.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Prior research has primarily focused on coaching models 10,47 and on the effects of coaching on the trainees being coached. 12,16,18,20,48,49 Recently, a few studies 21,23 21 which demonstrated the importance of community for coach learning. 50 Our findings go further and highlight the multiple communities in which coaches learned across their landscapes of practice.…”
Section: Discussionmentioning
confidence: 99%
“…Self-efficacy functions as an individual's energy to drive effort and persevere in achieving predetermined results. Self-efficacy is a faculty motivator that is strongly associated with job satisfaction and negatively with burnout [3]. Self-efficacy is the basis for individuals to give birth to innovation and creativity alternatives.…”
Section: Introductionmentioning
confidence: 99%